A Pilot Study of an Acceptance-based Behavioral Treatment for Binge Eating Disorder - Juarascio, Adrienne S. (J Contextual Behav Sci, 2017)
While existing treatments produce remission in a relatively large percentage of individuals with binge eating disorder (BED), room for improvement remains. Interventions designed to increase emotion regulation skills and clarify one’s chosen values may be well-suited to address factors known to maintain BED. The current study examined the preliminary efficacy of a group-based treatment, Acceptance-based Behavioral Therapy (ABBT), in a small open trial (n=19), as well as the relationship between changes in hypothesized mechanisms of action and outcomes. ABBT includes the behavioral components of cognitive behavioral treatment for BED and emotion-focused strategies from acceptance and commitment therapy and dialectical behavioral therapy. Results from generalized linear multilevel modeling revealed significant fixed linear effects of time on depression, quality of life, global eating pathology, and binge frequency (all ps < .05). Global eating disorder symptoms appeared to improve rapidly from pre- to mid-treatment, and continued to improve toward post-treatment and follow-up, but at a slower rate. Binge frequency decreased rapidly from pre- to mid-treatment, followed by a slight increase at post-treatment and a reduction again by follow-up. Improvements in experiential acceptance were strongly and consistently related to decreases in overall eating pathology across several measures (rs = .35–.54). Additionally, greater access to emotion regulation strategies was strongly related to decreases in overall eating pathology (r= .67). Preliminary results support the efficacy of this novel treatment approach and indicate that additional research on ABBT for BED is warranted.